IMPLEMENTASI TRAFFIC MANAGEMENT PLAN PADA PEKERJAAN REKONSTRUKSI PERKERASAN KAKU JALAN TOL (LAJUR 1 ZONA 1 KM 87+350 S/D 98+275 JALAN TOL CIKOPO–PALIMANAN TAHUN 2024 PAKET 1) - Satrio, Rio; Kholiq, Abdul (Universitas Majalengka, 2025)
One of the main infrastructures that supports people's mobility and economy is roads. Roads play a role in connecting various regions, facilitating the movement of people, goods, and services, and being the main driver of economic growth, so road safety and security are very important to consider. In the 2024 Cikopo-Palimanan toll road widening project, especially in the Rigid Pavement Reconstruction work, the safety of construction workers and road users is very important. Therefore, in this rigid pavement reconstruction work, the Traffic Management Plan (TMP) system is implemented to anticipate traffic accidents and construction accidents. The method used in the implementation of this practical work is the literature study method and field study on the 3rd Lane Widening project of the Cikopo-Palimanan Toll Road KM 87+350 to KM 98+275. The implementation of this Practical Work was carried out on the 3rd Lane Widening Project at KM 87+350 to KM 98+275 of the Cikopo - Palimanan Toll Road in 2024 Package 1 located in Subang. Traffic management arrangements and completeness of traffic signs in the 3rd Lane Widening project at KM 87+350 to KM 98+275 of the Cikopo - Subang Section, Cikopo - Palimanan Toll Road have been implemented properly in accordance with the Regulation of the Minister of Transportation in 2014 concerning Traffic Signs, so as to minimize the risk of traffic accidents at the project location.